Understanding the Past to Unpack the Present: Lessons from the Classroom - Kalyani Thurairajah (Journal of the Scholarship of Teaching and Learning)
Teaching courses pertaining to race and ethnic relations can be difficult due to the nature of the topics being discussed. One approach to help ease students into the course material is to anchor the content within a historical framework. However, this approach can be challenging within a Canadian context, where school curriculum prior to university often centralizes a narrative of multiculturalism at the expense of a narrative of racism. This paper draws on survey data collected from students in a third-year Sociology of race and ethnic relations course in western Canada as well as course assignments over a seven-year period to consider how topics like race, racialization and racism can be taught when there is a lack of shared understanding of the history of race relations.